One silent night - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- Dark-hunter novel., 2008)
While mortals deck the halls and shop, an angry demon lord is plotting an all-out onslaught against the entire human race. Enter Stryker, the adopted brother of the legendary Dark-Hunter, Acheron. As Stryker prepares to engage in battle against the ultimate predator he must also face the deadly rage of his ex-wife, Zephyra.